Effect of additional side groups on the vibrational frequencies of benzoquinone molecules - Raut, Nabin Kumar; Lamichhane, Hari Prasad (BIBECHANA, 2016)
The present work enumerates detailed computational investigation into the IR spectra in gas phase and in solvent of 1, 4- Benzoquinone family (benzoquinone (BQ), duroquinone (DQ), plastoquinone (PQ), ubiquinone (UQ), and dimethoxy dimethyl benzoquinone (MQo)). In  the spectra of BQ, PQ, and DQ, we observed separate intense carbonyl (C=O) and C=C bands respectively around 1730 cm-1 (intense), 1645 cm-1 (weak). On the other hand, for UQ and MQo, three prominent bands around 1652, 1703, and 1733 cm-1 were observed, where two C=O modes were uncoupled but one of the carbonyl is strongly coupled with C=C vibrations. The additional methyl groups downshift the intense carbonyl bands and upshift C=C mode frequencies. The carbonyl modes further downshifted in the solvent phase calculation.BIBECHANA 14 (2017) 66-76